Anthropocene Antarctica Perspectives from the Humanities, Law and Social Sciences. - Leane, Elizabeth; McGee, Jeffrey (Milton : Routledge, 2019)
Anthropocene Antarctica offers new ways of thinking about the Continent for Science and Peace' in a time of planetary environmental change. In the Anthropocene, Antarctica has become central to the Earth's future. Ice cores taken from its interior reveal the deep environmental history of the planet and warming ocean currents are ominously destabilising the glaciers around its edges, presaging sea-level rise in decades and centuries to come. At the same time, proliferating research stations and tourist numbers challenge stereotypes of the continent as the last wilderness.' The Anthropocene brings Antarctica nearer in thought, entangled with our everyday actions. If the Anthropocene signals the end of the idea of Nature as separate from humans, then the Antarctic, long considered the material embodiment of this idea, faces a radical reframing. Understanding the southern polar region in the twenty-first century requires contributions across the disciplinary spectrum. This collection paves the way for researchers in the Environmental Humanities, Law and Social Sciences to engage critically with the Antarctic, fostering a community of scholars who can act with natural scientists to address the globally significant environmental issues that face this vitally important part of the planet.
Final reflections on a fragile continentNotes; References; PART 3: Inhabitations and place; 9. Indigenising the heroic era of Antarctic exploration; Traditional knowledge and Antarctic exploration; Indigenous technologies; Indigenous inhabitants?; An absent presence; Conclusions; Notes; References; 10. Populating Antarctica: Chilean families in the frozen continent; Commercial exploitation of Antarctica?; The project becomes reality; Antarctic families, Antarctic babies; Living on the icy continent; Unexpected friendships; Conclusions; Notes; References
Description based upon print version of record.
11. Placing the past: The McMurdo Dry Valleys and the problem of geographical specificity in Antarctic history
OCLC-licensed vendor bibliographic record.
Keywords: NATURE / Ecology; POLITICAL SCIENCE / Public Policy / Environmental Policy; Climatic changes -- Antarctica; Nature -- Effect of human beings on -- Antarctica; Antarctica; Antarctica -- Environmental conditions